Gust factors for tropical cyclone, monsoon and thunderstorm winds. Issue 142 (July 2015) - Shu, Z.R.; Li, Q.S.; He, Y.C.; Chan, P.W.
Abstract: Gust factor, defined as the ratio of peak gust wind (of a given duration) to mean wind speed (for a given averaging time), is an important parameter for describing the turbulence characteristics of wind flows. Such information is useful for structural design, prevention of air pollution, air ventilation assessment and prospection of wind farms, etc. This study presents a comprehensive investigation on the characteristics of gust factor in tropical cyclones, monsoons and thunderstorms. Based on a 6-year wind database recorded at 6 meteorological stations in Hong Kong, the relations of gust factor with various wind parameters are explored. It is found that, in general, the variation of gust factor depends greatly on mean wind speed. This paper focuses on the comparison of gust factor in connection with tropical and extra-tropical winds, which shows that the deviation of gust factors is related to topographic condition and wind speed. The characteristics of gust factor associated with thunderstorm events are also investigated, and it is found that thunderstorms may generate larger statistic maximum values of gust factor when compared with those during strong synoptic winds. The dependence of gust factor against different gust durations are comparatively established, which implies that the time scales for thunderstorms are markedly different from those of tropical cyclones and monsoons. Finally, the correlation of gust factor with turbulence intensity is presented and discussed.